The evolution and diversity of TNF block haplotypes in European, Asian and Australian aboriginal populations - Valente, F.; Tan, C.; Temple, S.; Phipps, M.; Witt, C.; Kaur, G.; Gut, I.; McGinn, S.; Allcock, R.; Chew, C.; Price, Patricia (2009)
The region spanning the tumour necrosis factor (TNF) cluster in the human major histocompatibility complex is implicated in susceptibility to immunopathological disease, but ethnic differences and linkage disequilibrium have hampered identification of critical polymorphisms. Here, we investigate Europeans, Asians (Bidayuh, Chinese, Indian, Jehai, Malay, Temuan) and Australian Aborigines to provide a framework for disease-association studies. DNA from 999 unrelated healthy donors was genotyped at 38 loci, primarily in coding and promoter regions over a 60-kb region spanning seven genes near TNF. The PHASE algorithm was used to statistically infer TNF block haplotypes and estimate their frequencies in each population. The TNF block is carried as 31 haplotypes in all populations combined, with < 19 in any single population. Only six haplotypes have a unique tag single nucleotide polymorphism (SNP) valid for all populations, but seven haplotypes could be tagged with individual SNPs in selected populations. Four to eight TNF block haplotypes exist across all ethnicities, and hence must pre-date the divergence of these populations from a common ancestor >160000 years ago. Some haplotypes are unique to isolated populations, but they do not contain unique SNP. Hence, they reflect restricted migration and/or extinction of some families rather than de novo mutation.